SMA Negeri 1 Dempet, Kabupaten Demak Jawa Tengah - Machin, Achmad (Bioedukasi: Jurnal Pendidikan Biologi, 2012)
This research aimed to identify a model of biotechnology teaching used by Senior Highschools, to develop a model of entrepreneurship-based biotechnology teaching and to identify the effect of the model on students learning achievement, entrepreneurship attitude. The design of research involved using research and development (R&D) paradigm, consisted of 3 major steps, namely conducting an introductory research focussing on need analysis, developing a model of entrepreneurship-based biotechnology teaching, and then finally evaluating the efficiency of model. The findings showed that models of biotechnology teaching at Demak Senior Highschools did not yet satisfy the principles of School Competency-based Curriculum (KTSP). A model of entrepreneurship teaching was then necessary to develop, including its silabus & lesson plan, learning resources, student worksheets. The effect of the model upon students learning was significantly high. There was significants difference in cognitive as well as psychomotoric learning achievement between control and treatment groups. The effect of the model upon students attitude towards entrepreneurship was significantly high. There was significant difference of attitude between control and treatment groups. The average attitude of treatment group was 90. The effect of the model on students process of learning (learning activities) was also significant significant, their average activity was 86,5 (very high), the average of teachers activities was significant (88,30), and classroom-based learning assessments results was 82,8 (high). Majority of students (95%) felt happy with the model of teaching, because it improved their attitude toward entrepreneurship was also improved. Student felt as if they were entrepreneur.